The Aalborg process and its Hungarian connections - Baják, Imre (Acta Agraria Debreceniensis, 2006)
The four European Conferences on Sustainable Cities and Towns gave birth to documents that are important from the point of view of local sustainability. These are, in chronological order, the Aalborg Charter – 1994 Aalborg, the Lisbon Action Plan – 1996 Lisbon, the Hannover Call – 2000 Hannover, and the Aalborg Commitments – 2004 Aalborg. Throughout the process, the emphasis gradually moved from planning to the implementation of plans. Today, there are more than 2000 signatories of the Aalborg 1A tanulmány az OTKA T-046704 sz. pályázatának támogatásával készült. Charter. The cutting edge of the process are Italy and Spain, the municipalities of these two countries add up to 80 per cent of all signatories. In both countries, the national commitment is given, but there is not a body that could coordinate the activities related to sustainability, so local governments play the major role in it. The constitutions of these two countries also pass on some duties that are relevant from the point of view of sustainability within the competence of local governments, and allow resources to implement them. In the case of the United Kingdom, the commitment of the national government, and especially the Prime Minister, is the major factor in the movement towards local sustainability. The former socialist countries in Europe, as well as Hungary are relatively underdeveloped economically, so the social and environmental pillars of sustainable development are pushed into the background behind the economical pillar. As a result of the lack of national commitment, there is no guidance and there are no case studies available, so only a small part of local governments are informed of this important international movement, and so are committed to it. The lack of resources is also a problem. The consequence of all this is that there are 35 municipalities from the Eastern European countries that joined the EU in 2004, and only four from Hungary – to mention by name Aba, Kecskemét, Monor and Nagykanizsa – that signed the Aalborg Charter.